Transformasi Atribut Menjadi Elemen Estetis Pada Kostum Olahraga - Musnur, Irfandi (Universitas Komputer Indonesia, 2023)
The use of sports jersey T-shirt products has become a stylish variant of the fashion trend for the community. Users of this t-shirt product have penetrated several circles, both children, teenagers and the elderly. What's interesting is that the jersey basically has attribute components that are produced as function demands, now present as an aesthetic visual ornament in fashion. This research basically comes as a follow-up research that has been done before. Previous research has revealed that there is an additional function of the soccer jersey, both in terms of supporters as a fan identity and a marker for the players themselves. In this study, we try to look at it from a different perspective, namely the form of the transformation function of sports jersey attributes (not limited to football) into aesthetic attributes in the World of Fashion. This will be explained through the aspects of material, visual, color and other functions which are usually used as a function of transforming into a fashion trend. Through the research that has been done, it is concluded that the transformation of Functional Motivation into aesthetics in sports jersey fashion products is a process of sign association. The association involves the role of previous markers (such as color, other attributes and visuals) that have been established in the mind. Through this empirical knowledge it is conceptualized into a